Management Accounting as a Strategic Tool for Public Value in the Higher Education Sector - Ahmad, Fandi; Rubio, Luiz; Fitriani, Anandha (Startupreneur Business Digital (SABDA Journal), 2026)
This study explores the role of management accounting and control systems (MACS) as conceptualized through Simons Levers of Control framework in supporting public value creation, contributing to the growing body of literature on public value accounting. Adopting a mixed-method case study approach, which includes document analysis and semi structured interviews, the research uncovers varied applications of control systems within a Dutch university of applied sciences. The findings reveal a divergence in how control mechanisms are utilized. Belief systems and interactive control systems are employed extensively to facilitate strategic change and support the implementation of new strategic directions. In contrast, diagnostic control systems are primarily used at decentralized levels, functioning mainly as instruments to ensure compliance with operational and financial constraints. As such, belief and interactive controls form the core mechanisms for embedding public value considerations within the institution’s strategic orientation, while diagnostic controls serve to regulate activities at the operational level. Additionally, although the institution emphasizes the importance of engaging with external stakeholders, such interactions predominantly occur during the strategy formulation phase, with limited involvement observed during interim evaluations of the strategy, thereby refining the Levers of Control framework in the context of public value creation and demonstrating that contextual and unbalanced control configurations can effectively support public value orientation in higher education.